Etyka w pracy audytora wewnętrznego - Krawczyk, Marzena; Sekuła, Piotr (Annales. Etyka w Życiu Gospodarczym, 2008)
Internal audit provides an independent and objective opinion to the Boardon risk management,control and governance, by measuring and evaluating their effectiveness in achieving an organisation’sagreed objectives. It also provides an independent and objective consultancy service to help linemanagement improve the organisation’s processes.Internal auditors should respect in their work some ethical rules, especially these included inthe Code of Ethics formed by the IIA. This code is intended to clarify the standard of conduct expectedfrom all members of the internal audit unit. The main four principles that should be observed areas follows: integrity, objectivity, competency and confidentialityBeing ethical in internal audit is necessary in order to win the trust of the environment in whichauditors work. However, declaring one’s readiness to respect the Code of Ethics is not enough. Muchmore important is to implement and comply with given rules in carrying out audit duties.